Barriers and enablers to testing for hepatitis C virus infection in people who inject drugs - a scoping review of the qualitative evidence - Cathy R. Balsom; Alison Farrell; Deborah V. Kelly (BMC, 2023)
Abstract Background Injection drug use is the primary mode of transmission of hepatitis C virus (HCV) infection in the developed world and guidelines recommend screening individuals with current or history of injection drug use for HCV; however, the majority of those living with HCV in Canada are not aware of their positive status. This low level of HCV status awareness suggests that screening is not effective with current testing strategies. The aim of this review is to determine what barriers and enablers people who inject drugs (PWID) experience surrounding testing for HCV to help inform the development of an engaging testing strategy. Methods Comprehensive literature searches were conducted using Medline, Embase and CINAHL in February 2021. Included studies investigated the barriers and enablers to testing for HCV in PWID and the experiences of PWID in testing for HCV. Studies were included if they were qualitative or mixed-methods design, involved people with current injection drug use or those with a history of injecting drugs, and were written in the English language. Studies were compared and common themes were coded and analyzed. Results The literature search resulted in 1554 citations and ultimately nine studies were included. Common barriers included self-perception of low risk for HCV, fear of diagnosis, stigma associated with IV drug use and HCV, antipathy in relation to mainstream health care services, limited knowledge about HCV, lack of rapport with provider, lack of motivation or competing priority of drug use, and limited awareness of new treatment options. Common enablers to testing included increasing awareness of HCV testing and treatment and providing positive narratives around HCV care, positive rapport with provider, accessible testing options and individualized care. Conclusion While there has been some qualitative research on barriers and enablers to testing for HCV in PWID more research is needed to focus on this research question as a primary objective in order to provide more understanding from the participant's perspective.